Confinement-induced nanocrystal alignment of conjugated polymer by the soft-stamped nanoimprint lithography - 李晓慧 俞计成 陆乃彦 张卫东 翁雨燕 顾臻 (Chinese physics B, 2015)
Soft-stamped nanoimprint lithography（NIL） is considered as one of the most effective processes of nanoscale patterning because of its low cost and high throughput. In this work, this method is used to emboss the poly（9, 9-dioctylfluorene）film. By reducing the linewidth of the nanogratings on the stamp, the orientations of nanocrystals are confined along the grating vector in the nanoimprint process, where the confinement linewidth is comparable to the geometrical size of the nanocrystal. When the linewidth is about 400 nm, the poly（9, 9-dioctylfluorene）（PFO） nanocrystals could be orderly arranged in the nanogratings, so that both pattern transfer and well-aligned nanocrystal arrangement could be achieved in a single step by the soft-stamped NIL. The relevant mechanism of the nanocrystalline alignment in these nanogratings is fully discussed. The modulation of nanocrystal alignment is of benefit to the charge mobilities and other performances of PFO-based devices for the future applications.